The Intersection of Diet Quality and Ultraprocessed Food Intake: Using Evidence-Based Categories to Characterize Differences in Cardiometabolic Profiles. - Sheinberg, Elise; Schmidt, Laura A.; Mande, Jerold R.; Martinez-Steele, Euridice; Tobias, Deirdre K.; Leung, Cindy W. (American Journal of Public Health, 2026)
Objectives. To examine how ultraprocessed food (UPF) consumption and diet quality jointly relate to cardiometabolic health. Methods. This serial cross-sectional study used data from 15 760 US adults (aged ≥ 20 years) in the 2009–2018 National Health and Nutrition Examination Surveys. Participants completed two 24-hour recalls and did not have a chronic disease. Diet quality was categorized using Healthy Eating Index–2020 (HEI) scores as high (70 to 100), moderate (60 to < 70), low (50 to < 60), and very low (0 to < 50). UPF consumption, determined by Nova classification, was categorized as high (≥ 40% energy intake) and low (< 40% energy intake). Joint HEI–UPF categories combined these variables. We examined unadjusted and adjusted associations between joint HEI–UPF category and anthropometric and cardiometabolic biomarkers. Results. Among US adults, only 0.3% had high HEI–low UPF consumption, while 45.3% had very low HEI–high UPF consumption. Those with very low HEI–high UPF intake had the least favorable metabolic profiles, including the highest mean body mass index (29.6, defined as weight in kilograms divided by the square of height in meters) and fasting glucose (106.2 milligrams per deciliter). Conclusions. Diet quality was more consistently associated with cardiometabolic health than UPF intake. Public Health Implications. Overall diet quality is a strong predictor of cardiometabolic health, even with varying UPF consumption. (Am J Public Health. 2026;116(7):993–1003. https://doi.org/10.2105/AJPH.2026.308494)